THE STUDY OF DIRECTED FERMENTATION PROCESS USING STRAINS OF LACTIC ACID BACTERIA FOR OBTAINING VEGETABLE PRODUCTS OF STABLE QUALITY - V. V. Kondratenko; O. Yu. Lyalina; N. E. Posokina; V. I. Tereshonok (Овощи России, 2016)
The objective of the research was to study the process of directed fermentation of whitehead cabbage variety ‘Slava’, using strains of lactic acid bacteria and their consortium with the degree of their mutual influence. As strains of lactic acid bacteria, we have chosen the following: VCR 536 Lactobacillus casei, Lactobacillus plantarum VKM V-578. To obtain comparable results, all experiments were performed on model mediums. For the first time we studied the dynamics of changes in quality indicators at the process of directed fermentation using strains of lactic acid bacteria (LAB) including their consortiums. The mathematical model developed adequately describes the degree of destruction of glucose and fructose in the fermentation process. The raw material was undergone to homogenization and sterilization with the aim to create optimal conditionsfor the development of the target microorganisms and to detect the degree of  restruction of fructose and glucose by different strains of microorganisms. The mathematical model developed adequately described the degree of destruction of fructose and glucose in the treatment process. The use of a consortium of lactic acid bacteria (L. plantarum+L. casei) to this culture medium is shown to be impractical. The addition of fructose in quantity 0.5% to weight of the model medium enabled to intensify significantly the process of white cabbage fermentation.